The Influence of Internal Control Systems and Compensation on Fraud Tendencies in the Fraud Triangle Perspective - Suhroji Adha; Giantoro Pamungkas (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research aims to empirically test the influence of the internal control system on fraud tendencies, the effect of compensation on fraud tendencies empirically, and the influence of internal control and compensation simultaneously (together) on fraud tendencies in the fraud triangle perspective. This research uses a quantitative approach with data collection techniques using questionnaires. Based on the research, the population used in this study was 143 Serang Regency Agriculture Service employees. In contrast, the sample used a saturated sampling technique, which is when all population members are used as samples, so the sample taken in this study was 143 people. The results of this research are in hypothesis 1 that there is a significant influence between the internal control system and the tendency to fraud from a fraud triangle perspective. In hypothesis 2, a significant influence exists between compensation and the tendency to fraud from a fraud triangle perspective. In hypothesis 3, there is an influence between the internal control system and compensation on the tendency to fraud in the fraud triangle perspective.